High-throughput sequencing reveals hub genes for human early embryonic development arrest in vitro fertilization: a pilot study - Zhang, Wuwen; Li, Kai; Li, Shifeng; Lv, Rong; Ma, Jie; Yin, Ping; Li, Li; Sun, Ningyu; Chen, Yuanyuan; Lu, Lu; Li, Yun; Zhang, Qinhua; et al. (Frontiers in Physiology, 2023)
Many clinical studies have shown that embryos of in vitro fertilization (IVF) are often prone to developmental arrest, which leads to recurrent failure of IVF treatment. Early embryonic arrest has always been an urgent clinical problem in assisted reproduction centers. However, molecular mechanisms underlying early embryonic development arrest remain largely unknown. The objective of this study is to investigate potential candidate hub genes and key signaling pathways involved in early stages of embryonic development. RNA-seq analysis was performed on normal and arrest embryos to study the changes of gene expression during early embryonic development. A total of 520 genes exhibiting differential expression were identified, with 174 genes being up-regulated and 346 genes being down-regulated. Up-regulated genes show enrichment in biosynthesis, cellular proliferation and differentiation, and epigenetic regulation. While down-regulated genes exhibit enrichment in transcriptional activity, epigenetic regulation, cell cycle progression, cellular proliferation and ubiquitination. The STRING (search tool for the retravel of interacting genes/proteins) database was utilized to analyze protein-protein interactions among these genes, aiming to enhance comprehension of the potential role of these differential expression genes (DEGs). A total of 22 hub genes (highly connected genes) were identified among the DEGs using Cytoscape software. Of these, ERBB2 and VEGFA were up-regulated, while the remaining 20 genes (CCNB1, CCNA2, DICER1, NOTCH1, UBE2B, UBE2N, PRMT5, UBE2D1, MAPK3, SOX9, UBE2C, UB2D2, EGF, ACTB, UBA52, SHH, KRAS, UBE2E1, ADAM17 and BRCA2) were down-regulated. These hub genes are associated with crucial biological processes such as ubiquitination, cellular senescence, cell proliferation and differentiation, and cell cycle. Among these hub genes, CCNA2 and CCNB1 may be involved in controlling cell cycle, which are critical process in early embryonic development.